O conflito armado e a violência no Peru sob a ótica da Comisión de la Verdad y Reconciliación: informe final (1980 a 2003) - Angelo Anderson Andrade Coimbra (2015)
This study aims to analyze and understand the official version prepared by the Comisión de la Verdad y Reconciliación. Informe Final (CVR) on the armed conflict in Peru during the period between 1980 and 2000. In 1980, the Communist Party of Peru Sendero Luminoso (PCP-SL) started the armed struggle against the State in order to achieve powerpolitician in the country. The process of violence intensified after the insertion of the government law enforcement, especially the armed forces, in combating guerrillas still in the 1980s. We developed a critical analysis of the armed groups involved in the conflict: PCP-SL, police, Armed Forces and Self-Defense Committees, in order to understand howtheir actions contributed to the process of violence. About the PCP-SL, considered by CVR as the main actor in the conflict, we present its rising, its ideological and political configuration and the way it, before the beginning of the conflict, acted in Peru. We seek to understand how the Transitional Justice process occurred in a country that hasexperienced periods of violence and violation of human rights and what were the contributions and importance of the Truth Commission in Peru. We also analyzed the creation of the CVR and the result of its work published in the form of text the Final Report pointing the profile of professionals who composed the CVR and what work was adopted by it to carry out and ensure the Peruvian society the right to truth, memoryand justice. For this, we also seeked to understand some key terms in the reading of the Final Report, namely: truth, victims and witness. For the CVR, the testimonial narratives make up the main source of analysis and "truth" of the events. Therefore, our research examined how the CVR incorporated the stories of witnesses in the construction of theReport and the national reconciliation proposals put forward by this committee and how they became part of the program of action in the Integral Plan of Reparations.